Improving Arabic Typing Competence through the Rapid Typing Application - Ahmad Rizki Nugrahawan; Yulia Rahmawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The Rapid Typing application is an application to learn Arabic typing that makes users more quickly master the techniques and the correct way of typing. The method of implementing this community service activity is in the form of direct training which is carried out in 3 meetings. This activity is divided into four stages, namely First, reflection, and first material, students are given material related to the use of technology in learning. Second, the provision of materials related to digital-based writing competence and Rapid Typing. Third, FGD is a form of deepening the material and practice of writing training with Rapid Typing. Fourth, question and answer and evaluation. The results of this activity are expected to be able to increase understanding of the use of technology for learning for students and can improve digital Arabic writing/typing competence for students at SMA Muhammadiyah Cileungsi so that it becomes an additional soft skill for them. The results of this community service activity were attended by 36 students. the participants admitted that they had gained new knowledge and felt an increase in their Arabic typing skills with the rapid typing application. The desire to continue practicing Arabic typing using the rapid typing application after participating in this community service is quite large. Therefore, the role of the Arabic language teacher is expected to be able to teach or provide time for students to continue practicing typing with Rapidtyping so that their potential continues to be explored and increased